2016
DOI: 10.1016/j.jcf.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

CFTR potentiator therapy ameliorates impaired insulin secretion in CF patients with a gating mutation

Abstract: The treatment with ivacaftor in patients with CF carrying gating mutation can ameliorate impaired insulin secretion. Further studies and larger cohorts are needed to evaluate the impact of ivacaftor on insulin secretion in patients with CF carrying gating or other mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 8 publications
1
36
1
1
Order By: Relevance
“…The second study reported lower glycemic variability upon GCM at 6 months post-treatment in nine CF subjects with early AGT [7] . Other small studies reported a positive effect of ivacaftor on glucose metabolism in CF patients with G551D or Delta F508/S549R mutations [8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 94%
“…The second study reported lower glycemic variability upon GCM at 6 months post-treatment in nine CF subjects with early AGT [7] . Other small studies reported a positive effect of ivacaftor on glucose metabolism in CF patients with G551D or Delta F508/S549R mutations [8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 94%
“…There is some evidence to suggest that ivacaftor improves pancreatic endocrine function and sinus disease. [108][109][110][111][112][113] However, it is unclear whether CFTR modulator therapy will permit some chronic maintenance therapies to be safely discontinued to reduce treatment burden, which is currently overwhelming and untenable for many patients. 147 GLOSSARY Adeno-associated vector (AAV): A small virus that infects humans without causing disease.…”
Section: Guidelinesmentioning
confidence: 99%
“…So far three small studies have reported improvement of insulin secretion and hyperglycemia after treatment with ivacaftor 1719 . Anecdotal reports of hypoglycemia in people treated with CFTR modulators suggest the need for caution and perhaps increased blood glucose monitoring after beginning treatment with a CFTR modulator medication.…”
Section: Cf-related Diabetesmentioning
confidence: 99%